2010
DOI: 10.1007/s12198-010-0055-y
|View full text |Cite
|
Sign up to set email alerts
|

A simulation modeling framework for community-wide evacuation planning

Abstract: Simulation is a useful and cost effective tool for evacuation planning. However, extensive data collection and preparation is necessary to build a traffic evacuation simulation model that can closely replicate real life conditions. In a community-wide evacuation process during an emergency, which covers hundreds of miles, input data related to simulation of traffic evacuations include (1) Traffic and roadway geometry, (2) Geographic distribution of the affected area, (3) Travel demand modeling, and (4) Behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In particular we analyse how relevant the Tsunami warning system was; aiming to expand on results discussed in Yun and Hamada (2015) or Suppasri et al (2013). Previous research has shown that responses to evacuation orders and warnings differ (Duanmu, Chowdhury, and Taaffe 2011). Our third questions is whether "field effects" are significant, that is, how important the influence of others is on evacuation.…”
Section: Questionsmentioning
confidence: 99%
“…In particular we analyse how relevant the Tsunami warning system was; aiming to expand on results discussed in Yun and Hamada (2015) or Suppasri et al (2013). Previous research has shown that responses to evacuation orders and warnings differ (Duanmu, Chowdhury, and Taaffe 2011). Our third questions is whether "field effects" are significant, that is, how important the influence of others is on evacuation.…”
Section: Questionsmentioning
confidence: 99%
“…In addition, Duanmu et al. () presented a framework for preparing simulation inputs, such as traffic and roadway geometry, a behavioural analysis of potential evacuees, and ultimately developing a simulation model for a community‐wide evacuation process during an emergency. This type of study attempted to determine rational community evacuation systems or ways to identify the rational systems with the use of software such as geographic information systems (GIS) or simulators like the spot oriented agent role simulator (SOARS).…”
Section: Previous Efforts Toward Safer Community Evacuationmentioning
confidence: 99%
“…Many of these studies employed traffic simulation software to better evaluate traffic patterns and load during primarily evacuation events. There have also been studies to investigate disaster prevention measures for evacuation plans and to develop methods to reduce the evacuation time from disaster-stricken areas [8,9]. The studies that evaluated evacuation strategy methods tested lane-based routing [10,11] and contraflow [12] techniques.…”
mentioning
confidence: 99%